Service-oriented computing : 17th International Conference, ICSOC 2019, Toulouse, France, October 28-31, 2019, Proceedings /: 17th International Conference, ICSOC 2019, Toulouse, France, October 28-31, 2019, Proceedings. (2019) - Unknown
No abstract available